2005
DOI: 10.1016/j.immuni.2005.09.002
|View full text |Cite
|
Sign up to set email alerts
|

An Alternate Pathway for CD4 T Cell Development: Thymocyte-Expressed MHC Class II Selects a Distinct T Cell Population

Abstract: Conventional understanding of CD4 T cell development is that the MHC class II molecules on cortical thymic epithelial cell are necessary for positive selection, as demonstrated in mouse models. Clinical data, however, show that hematopoietic stem cells reconstitute CD4 T cells in patients devoid of MHC class II. Additionally, CD4 T cells generated from human stem cells in immunocompromised mice were restricted to human, but not mouse, MHC class II. These studies suggest an alternative pathway for CD4 T cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
132
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(140 citation statements)
references
References 56 publications
7
132
1
Order By: Relevance
“…The generally held belief is that the most efficacious method of T cell selection involves positive selection on MHCexpressing thymic epithelial cells (nonhematopoietic), followed by negative selection involving bone-marrow derived elements (17,18). However, this long-held view of exclusive T cell positive selection on radio-resistant thymic cells is under revision based on more recent studies suggesting that positive selection can occur on BM derived cells (10,(19)(20)(21), including fibroblasts or other MHC class II expressing cells in the thymic microenvironment (22)(23)(24). T cell development has also been shown to occur by extrathymic pathways (25,26).…”
Section: Mhc-restriction and T Cell Selectionmentioning
confidence: 99%
“…The generally held belief is that the most efficacious method of T cell selection involves positive selection on MHCexpressing thymic epithelial cells (nonhematopoietic), followed by negative selection involving bone-marrow derived elements (17,18). However, this long-held view of exclusive T cell positive selection on radio-resistant thymic cells is under revision based on more recent studies suggesting that positive selection can occur on BM derived cells (10,(19)(20)(21), including fibroblasts or other MHC class II expressing cells in the thymic microenvironment (22)(23)(24). T cell development has also been shown to occur by extrathymic pathways (25,26).…”
Section: Mhc-restriction and T Cell Selectionmentioning
confidence: 99%
“…18 The concept of multiple avenues of T-cell maturation in the thymus, mediated via thymic epithelial cells, thymocytes or as yet undefined lineages would explain why patients with MHC Class II deficiency can support thymopoiesis and T-cell reconstitution (albeit partial in many cases) after transplantation despite persistent deficiency of MHC II expression in non-haematopoietic lineages. 20 It should be noted that all surviving patients in this study remained deficient in naive T-cell numbers. In the HLA-matched family donor setting, transfer of mature donor T cells expanding in the recipient may contribute to more rapid reconstitution, in contrast to T-cell-depleted transplants, where T-cell reconstitution resides predominantly on de novo thymopoiesis.…”
Section: Chimerismmentioning
confidence: 74%
“…16,17 Recently, our group and others have reported a new distinct subset of innate abT cells (T-T CD4 T cells), which are selected by MHC class II-expressing thymocytes and also depend on PLZF for their development. [28][29][30] Moreover, we reported that the generation of T-T CD4 T cells is a physiological process in humans. 18 Up to now, PLZF has been exclusively expressed in a variety innate T cells including innate gdT cells, type I and type II NKT cells, MAIT cells, and T-T CD4 T cells in lymphoid system.…”
Section: Discussionmentioning
confidence: 99%